2021
DOI: 10.1002/tqem.21788
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of whey and its permeate using a genetically modified strain of Escherichia coli K12 MG1655 to produce 2,3‐butanediol

Abstract: Whey is generated during cheese manufacturing, and permeate whey is obtained after whey deproteinization. Both effluents contain lactose, which can cause environmental issues if they are released into the environment. The aim of the present study was the valorization of lactose contained in whey and permeate whey via fermentation into 2,3‐butanediol (2,3‐BD) with genetically modified strain of Escherichia coli K12 MG1655. Both effluents were first fermented at various dilution ratios with the culture medium M9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Indeed, there are heat-resistant pathogens within the detected bacteria that may cause serious illness: diarrheal and emetic diseases for people even after heating the milk 39 . All E. coli isolates were subjected to fecal coliform test and our data found that the obtained isolates were able to ferment lactose and form gas when incubated at 44 °C for 24 h. This proved that all obtained E. coli isolates were fecal isolates which transmitted from the pond water through the larvae and passed to adults through the larvae’s developmental stages and retransmitted it to the sterilized milk while feeding through their midguts 40 . According to ISO requirements in dairy product factories receiving milk shipments from live stocks, infected milk with fecal E. coli will subject these shipments to rejection and this loss economically affects milk producers in urban villages 41 .…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, there are heat-resistant pathogens within the detected bacteria that may cause serious illness: diarrheal and emetic diseases for people even after heating the milk 39 . All E. coli isolates were subjected to fecal coliform test and our data found that the obtained isolates were able to ferment lactose and form gas when incubated at 44 °C for 24 h. This proved that all obtained E. coli isolates were fecal isolates which transmitted from the pond water through the larvae and passed to adults through the larvae’s developmental stages and retransmitted it to the sterilized milk while feeding through their midguts 40 . According to ISO requirements in dairy product factories receiving milk shipments from live stocks, infected milk with fecal E. coli will subject these shipments to rejection and this loss economically affects milk producers in urban villages 41 .…”
Section: Discussionmentioning
confidence: 51%
“…The resulting strain, E. coli JFR12, was studied to produce 2,3-butanediol using whey and whey permeate. The genetically modified strain could be commercialized for high 2,3-BD production (up to 0.41 g/g lactose) under mild operating conditions [177].…”
Section: Acid Wheymentioning
confidence: 99%
“…Constructing microbial cell factories for the production of 2,3butanediol from biomass is considered as a strong alternative. Extensive studies have been carried out to develop e cient microbial cell factories for producing 2,3-butanediol, including Bacillus subtilis [9,10], Bacillus amyloliquefaciens [11,12], Bacillus licheniformis [13,14], Klebsiella oxytoca [15,16], Klebsiella pneumoniae [17,18], Paenibacillus polymyxa [19,20], Serratia marcescens [21,22], Enterobacter cloacae [23,24], Enterobacter aerogenes [25,26], Escherichia coli [3,27], Zymomonas mobilis [28] and Pichia pastoris [29], etc.. Signi cantly, the K. pneumoniae SDM isolated from orchard soil accumulated 150 g/L 2,3-butanediol at 38 h in a 5-L bioreactor, representing the highest titer achieved by the wild type [17]. However, most microorganisms with ability to naturally accumulate 2,3-butanediol produce a mixture of two of the three isomers ((2S,3S)-, (2R,3R)-, meso-2,3-butanediol) [2,30], which limits its application.…”
Section: Introductionmentioning
confidence: 99%